43 A Pilot Study of Pre-Operative Vestibular Low Intensity Shockwave Therapy to Decrease Opioid Use Post-Vestibulectomy. Issue 1 (1st April 2022) - Yee, A; Uloko, M; Goldstein, I
ABSTRACT: Introduction: Surgeons performing complete vestibulectomy with vaginal advancement flap reconstruction for suspected neuroproliferative vestibulodynia (NPV) take into consideration the need for acute pain relief in the early postoperative period as well as risks for persistent post-operative opioid use. Post-operative acute pain has traditionally been managed with narcotics which are effective but are highly addictive and can cause unwanted side effects including nausea/vomiting, impaired mental function, and severe constipation/obstipation. We serendipitously observed that one patient who tried to avoid surgery by undergoing numerous vestibular low intensity shockwave therapy (LiWST) treatments used very few narcotics post vestibulectomy. LiWST is FDA-cleared for pain amelioration. It has been hypothesized that LiSWT downregulates inflammatory cytokines, promotes enhancement of blood flow and angiogenesis through expression of vascular endothelial growth factor and nitric oxide synthesis. Objective: We performed a pilot study using pre-operative LiSWT to determine whether or not it might decrease post-operative opioid use (oxycodone/acetaminophen tablets; 5mg/325mg) for acute pain management in patients undergoing complete vestibulectomy with vaginal advancement flap for suspected NPV. Methods: We studied the post-op opioid use of women who underwent complete vestibulectomy at our facility during the period January 1, 2019 through June 30, 2021. We assessed opioid use based on the patient's recall of the total oxycodone/acetaminophen tablets required in the first 30 days post-vestibulectomy. When possible, patients confirmed the use by counting tablets left in the pill container. Women scheduled to undergo vestibulectomy for suspected NPV were placed in the LiSWT study group if they agreed to undergo vestibular LiSWT treatment daily for the three business days immediately pre-operatively. Using the Urogold 100™MTS, LiSWT involved delivery of 1800 shocks to the vestibule per session, energy flux density 0.05-0.1 mJ/mm2, 3 Hz, membrane pressure 3. We compared the post-op opioid use by women in the LiSWT study group to the use by women who did not undergo pre-op LiSWT. Results: Forty-five women (mean age 28 years; range 17 - 57) underwent complete vestibulectomy for suspected NPV during the 30 month period. Twenty women (mean age 27 +/- 9 years) agreed to undergo pre-op LiSWT and post-op opioid use was obtained in all. Twenty-five women (mean age 29 +/- 11 years) did not undergo pre-op LiSWT and opioid use was obtained in 19/25 (76%). Mean post-operative opioid use was 47 +/- 13 (range 25 - 90) tablets in those vestibulectomy patients who did not undergo pre-op vestibular LiSWT; opioid side effects included constipation, nausea, fainting, drowsiness, fatigue, and blurred vision. Mean post-op opioid use was 22 +/- 10 (range 1 - 26) tablets in the 20 vestibulectomy patients who did undergo pre-op vestibular LISWT sessions; opioid side effects were restricted to constipation, sleepiness, and nausea. Conclusions: In this pilot study, pre-operative low intensity shockwave therapy decreased post-operative opioid use after complete vestibulectomy with vaginal advancement flap. While encouraging, more research is needed. Disclosure: No